Blackout : how Black America can make its second escape from the Democrat plantation - Owens, Candace (Threshold Editions, 2020)
"Political activist and social media star Candace Owens explains all the reasons how the Democratic Party policies hurt, rather than help, the African American community, and why she and many others are turning right"--